A new species of Otiorhynchus from central Asia (Coleoptera: Curculionidae) - Luigi Magnano; Enzo Colonnelli (Fragmenta entomologica, 2014)
is described and illustrated the parthenogenetic species Otiorhynchus (Eprahenus) cooteri sp. n. from Kazakhstan and Uzbekistan, close to the amphigonic O. aksudshabaglinus Bajtenov, 1974 from an adjoining area of Kazakhstan. The new species is allied with other central asiatic O. (Eprahenus), with all of which is shortly compared, whereas other members of the subgenus occurring in the Caucasus and surrounding area appear rather distantly related with the ones here considered. Otiorhynchus kasakhstanicus Arnoldi, 1964 is moved to O. (Zariedus) Reitter, 1912 from O. (Eprahenus) Reitter, 1912.